Penetrating femoral artery injuries : an urban trauma center experience - Rayamajhi, Shreya (Department of Surgery, 2018)
INTRODUCTION: The femoral artery (FA) is the most common peripheral vessel injured in trauma. The incidence has been as high as 70%. Most experience with vascular trauma comes from the military where the incidence of FA injury is 67% of all vascular injuries. Up to 88% of these injuries are as a result of penetrating trauma. The Groote Schuur hospital trauma unit is a level one centre. It is a quaternary hospital and a referral center for all surrounding secondary level hospitals. Femoral vessel injuries are the second most common peripheral vascular injury (18.8%) seen after brachial artery injuries (48.2%) at our unit. AIM: This study aims to review a single centre experience with femoral artery injuries and identify factors associated with limb loss. METHOD: A 11 year retrospective chart review of patients with femoral artery injuries managed from 1 January 2002 to 31 December 2012 at the trauma unit, GSH. RESULTS: There were 158 patients with femoral artery injuries, 144 men and 14 women with a mean age of 28. Ninty-five percent had penetrating injuries. The most common artery injured was the superficial femoral artery (87%). The most common type of arterial injury was a laceration (39%) and transection (37%). Eighty-one patients had a primary repair (51%), fifty-three patients had a vein interposition graft (33.5%) and sixteen patients (10%) had a prosthetic graft. There were 78 (51%) concomitant venous injuries, 11 were repaired and 1 vein patch was done (15.4%). The rest were ligated (84.6%). There were 4 (2.5%) primary amputations and 10 (6.5%) secondary amputations. One primary amputation resulted from a delay to theatre with a threatened limb. The other three presented with a non-viable limb. Nine of the ten secondary amputations presented with a threatened limb. One viable limb was lost due to bleeding from a false aneurysm secondary to sepsis. One secondary amputation was the result of a delayed fasciotomy for compartment syndrome post revascularisation of a threatened limb. The rest were due to prolonged ischemic time despite attempted revascularization. There were no deaths in this study. Univariate analysis showed that statistically significant risk factors for secondary amputation were: presentation with signs of a threatened (ischemic) limb (p<0.0001), the temporary vascular shunt group (p<0.001) and the lack of a palpable distal pulse post repair (p<0.01). Statistically insignificant factors were: concomitant femur fracture, compartment syndrome, fasciotomy, unstable hemodynamics on presentation, venous ligation and 'In hospital ischemia time'. CONCLUSION: The outcome of threatened limbs due to femoral vessel injury is good provided there is no delay to surgery. This study has a primary amputation rate of 2.5% and secondary amputation rate of 6.5%, 91% of the limbs were salvaged.